Analisis Potensi Sumber Daya Manusia Untuk Pengembangan Usaha Peternakan Sapi Potong Di Kabupaten Pesisir Selatan - A. Suresti; R. Wati; I. Indrayani (Universitas Andalas, 2013)
This study aims to: (1). determined the potential of human resources (Breeders) for the development of beef cattle; (2). calculating employment opportunities based on the elasticity of employment. This research was conducted in Pesisir Selatan Regency, West Sumatra Province. The data was collected using a survey method. The population of this study were 99 RTP. The sampling method used simple random sampling technique. Analysis of the data used the qualitative and quantitative analysis deskriptif. The results showed that farmers in particular human resources in this area was not sufficient to develop their business in a better direction, it was seen from education and working hours for the beef cattle business in which 62.9% of farmers did not finish his formal education as well as technical knowledge still low despite having an average breeding experience of over 10 years. Time that the need to maintain a single head of cattle per day was 0.75 hours / cow / day or equal to 0.0938 HOK. Employment elasticity of 0.24. That was, if the Pesisir Selatan Regency GDP increased by one percent, there will be job creation livestock sector by 0.24 percent.